Diversity of Trypanosomatids in Cockroaches and the Description of Herpetomonas tarakana sp. n - Yurchenko, Vyacheslav; Kostygov, Alexei; Havlová, Jolana; Grybchuk-Ieremenko, Anastasiia; Ševčíková, Tereza; Lukeš, Julius; Ševčík, Jan; Votýpka, Jan (The Journal of eukaryotic microbiology, 2016)
In this study, we surveyed six species of cockroaches, two synanthropic (i.e. ecologically associated with humans) and four wild, for intestinal trypanosomatid infections. Only the wild cockroach species were found to be infected, with flagellates of the genus Herpetomonas. Two distinct genotypes were documented, one of which was described as a new species, Herpetomonas tarakana sp. n. We also propose a revision of the genus Herpetomonas and creation of a new subfamily, Phytomonadinae, to include Herpetomonas, Phytomonas, and a newly described genus Lafontella n. gen. (type species Lafontella mariadeanei comb. n.), which can be distinguished from others by morphological and molecular traits.
Keywords: taxonomy; parasites of cockroaches; RNA ribozomální 18S; švábi; Phylogeny; Monoxenous Trypanosomatidae; Sequence Analysis, DNA; protozoální DNA; DNA, Protozoan; Genotype; zvířata; Slovakia; Slovenská republika; sekvenční analýza DNA; biodiverzita; fylogeneze; Trypanosomatina; Czech Republic; polymerázová řetězová reakce; Polymerase Chain Reaction; Cockroaches; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; genotyp; Animals; RNA, Ribosomal, 18S; Česká republika; Biodiversity